THE SIGNIFICANCE OF LEADERSHIP SUPPORT TOWARDS EFFECTIVE CONTRACT MANAGEMENT (Journal of Technology and Operations Management, 2023)
This study examines the role of leadership support in contract management within the Ministry of Defence, focusing on the asset and equipment maintenance crucial for national security. It aims to assess the current level of leadership support among Supply & Secretariate Officers in the Royal Malaysian Navy and their understanding of its importance. By addressing this gap, this study intends to improve contract management practices for enhanced national security within the ministry. A quantitative survey was used to obtain data through stratified random sampling. The survey was initiated in April 2022 and lasted five months. The questionnaires were distributed to the Supply & Secretariate Officers who handle the asset and equipment maintenance contract of the Ministry of Defence. A total of 206 questionnaires were distributed through electronic means, such as email and WhatsApp. Out of 206 questionnaires, only 204 has been analysed as the other two were not complete. The results revealed that leadership commitment significantly improves contract-related activities. When top executives prioritize contract management, it creates a corporate environment in which rules are followed, responsibility is clear, and employees are more diligent. This commitment leads organizations to allocate resources, set clear contract guidelines, and invest in advanced contract technology, making contract management more efficient. In summary, leadership commitment fosters a culture of excellence in contract management, emphasizing the importance of contracts, compliance, and attention to detail, ultimately improving overall operational efficiency.